A CRITICAL DISCOURSE ANALYSIS OF ONLINE NEWS TEXTS: A CASE OF TRIBUN-TIMUR.COM - Soeharto, Muhamad; Hidayat, Didin Nuruddin; Alek, Alek; Septiawan, Yudi (Wiralodra English Journal, 2021)
This research aims to reveal the dimensions of texts, such as elements of representation, relations, and identity according to the Norman Fairclough discourse analysis displayed on the online news. This type of research is descriptive qualitative. Researchers began to analyze the data by reading the news of the February 2019 ATKP cadet death portal online, understanding the elements of the Norman Fairclough text dimension, and doing the technique to record the results in the reporting of the death of the ATKP cadet in February 2019. The reporting on the death of ATKP strains on February 9, 2019, entitled: Penganiayaan di Kampus Akademi Teknik Keselamatan Penerbangan (ATKP) dan Politeknik Ilmu Pelayaran (PIP) Kota Makassar, dinilai warga sekitar, sudah menjadi hal biasa, and on February 10, 2019, entitled: Sepekan taruna ATKP Makassar tewas dianiaya seniornya, begini penanganan kasusnya posted on the tribun.com website became the primary data in this research. The results showed that some elements of text dimensions are on the news, such as representation, relations, and identity. It was found that Tribun-timur.com was relatively proportional in reporting the pros and cons of the event.